(untitled) (Sains Humanika, 2016)
Nowadays, housing index not merely act as housing performance indicator but also been transformed into financial product that based on housing index. There are two issues to be considered in this paper which are temporal aggregation and seasonality problem in housing index. Seasonality appeared in time series when the price or index movement is repetitive around the trend line. If the housing index consists of seasonal effect it will mislead measurement on real housing performance based on economic situation. In other words, cyclical effect should be avoided in measuring housing performance. Temporal aggregation in constructing house price index may lead to missing information for certain periods and variability in house price is smooth. As a result, the evaluation on housing performance becomes unrealistic. In order to investigate these problems quality adjusted index will be developed by hedonic model based on Laspeyres, Paasche, Fisher and time dummy price index formula. The case study to be investigated is housing index of double storey houses in Plentong Johor. This study found that house price index that developed from different level of temporal aggregation will lead to different risk and return and seasonality effect is exist in house price index Plentong.